Self-reported cocaine use, emergency physician testing and outcomes in suspected acute coronary syndromes: a nested matched case–control study. Issue 3 (2nd June 2012) - Wang, Yang; Lindsell, Christopher J; Pollack, Charles V; Hollander, Judd; Diercks, Deborah B; Kirk, J Douglas; Anantharaman, Venkataraman; Gibler, W Brian; Hoekstra, James; Peacock, W Frank
Abstract : Objectives: The primary purpose was to compare the odds of acute coronary syndrome-pertinent diagnostic testing between self-reported cocaine users and non-users at the turn of the century. The secondary purpose was to compare the odds of acute coronary syndrome outcomes between cocaine users and non-users. Design: Nested matched case–control study using data from the Internet Tracking Registry of Acute Coronary Syndromes. Setting: Extracted data of patients from eight US institutions composed of six academic and two community hospitals, with census varying between 10 000 and 160 000 visits per year. Participants: 249 cases of self-reported cocaine users and 249 matched controls. Matching was based on age, race, sex and any history of known coronary artery disease. Exclusion criteria were new ST elevations on initial ECG and initial physician impression of acute myocardial infarction. Primary and secondary outcome measures: Primary outcome was the conditional odds of undergoing non-invasive and invasive testing for coronary artery disease. Secondary outcome was the occurrences of adverse cardiac outcomes within 30 days. Results: Cocaine users underwent diagnostic testing at similar rates compared with non-users (9.6% vs 8.0%, OR 1.24, CI 0.65 to 2.34). Adverse cardiovascular outcomes occurred in four (1.6%) cocaine users and in seven (2.8%) controls. Conclusions: There was no increase in tendency for testing associated with self-reported history of cocaine use between 1999 and 2001. This suggests that even 10 years ago, cocaine use already had only a limited role in the Emergency Department (ED) physician's decision-making process. Similar data analyses of detailed registries can offer important contextual information that can better direct resources for future comparative effectiveness research.